Cutaneous melanoma: hints from occupational risks by anatomic site in Swedish men. Issue 2 (22nd January 2004) - Perez-Gomez, B; Pollán, M; Gustavsson, P; Plato, N; Aragonés, N; López-Abente, G
Abstract : Aims: To improve knowledge of the epidemiology of melanoma by comparing occupational risks of cutaneous melanoma (CM) by anatomic site in Swedish workers. Methods: Male workers employed in 1970 and living in the country in 1960 were followed up from 1971 to 1989 using the Swedish Registers of Death and Cancer. A more specifically exposed subcohort included men reporting the same occupation in 1960 and 1970. For each location, occupational risk ratios (RRs) were extracted from Poisson regression models adjusted by age, period, town size, and geographical area. To diminish the influence of socioeconomic factors, intrasector analyses, comparing only jobs belonging to the same occupational sector, were performed. Risk patterns for different locations were compared. Results: High RRs for different sites were found among workers exposed to UV sources (dentists, physiotherapists, and lithographers), and sun exposed workers (harbour masters, and lighthouse/related work). Risk excesses were seen in fur tailors, tanners/fur dressers, patternmakers/cutters, electrical fitters/wiremen, telephone/telegraph installers/repairmen, and some glass/pottery/tile workers. Results for lower and upper limbs were significantly correlated but somewhat independent of those found in thorax, the most frequent location. Correlation between head/neck and thorax was moderate. Specific risk excesses were found for rolling mill workers in head/neck, for chimney sweeps in upper limbs, and for aircraft pilots/navigators/flight engineers in lower limbs. Conclusions: High RRs in the trunk among occupations with UV exposure from artificial sources suggest an effect not restricted to exposed sites. An unusual distribution of cases and RRs in chimney sweeps, rolling-mill, or glass/pottery/tile workers suggests local effects of exposures. The not previously reported risk excess in this job and in fur related processes, and the RR in electrical fitters and telephone/telegraph installers deserve further investigation. Disparities between locations, as RRs in thorax and limbs, may reflect differences in aetiological mechanisms.